PENGARUH MODEL PEMBELAJARAN PROBLEM-BASED LEARNING TERHADAP HASIL BELAJAR IPA DITINJAU DARI KEAKTIFAN SISWA - Pulung Zaelani (N A T U R A L: Jurnal Ilmiah Pendidikan IPA, 2016)
The research descriptively aimed to know the result of learning natural science and students activity at eight grade of SMP Negeri 10 Yogyakarta school in academic year 2014/2015 which learned using problem-based learning and direct instruction. Comparatively to determine the differences of learning science result between problem-based learning and direct instruction in terms of students activeness. The population of this research was 171 students. The sample was taken by purposive sampling technique. The data collected by documentation, a test of learning science and observation sheet. The hypothesis analysis technique used ANCOVA. Descriptively, the natural science result which learned by problem-based learning is in a very high category and direct instruction included in the high category. The studentsâ€™ activity which used problem-based learning is in high category and direct instruction included in the medium category. The ANCOVA test gained Fcount = 7,405. Therefore the result of FcountÂ  > Ftable comparatively there were significant differences of science learning result at grade VIII students in SMP Negeri 10 Yogyakarta between through problem-based learning and direct instruction that is seen from the student's activity.